Phy 300 pre-technical physics, course outline - Worthington, Roger G.; North Carolina State Dept. of Community Colleges, Raleigh ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1963)
Teachers developing lesson plans for a course in basic principles and concepts of physics can use this outline. It was developed by a committee of teachers and was based on experience and classroom use. The objective of the course is to help students acquire an understanding of the scientific approach and a working knowledge of basic laboratory procedures and equipment through units -- (1) general laboratory procedures, (2) properties and relationship of matter and energy, (3) systems of measurement, (4) force and motion, (5) friction, and (6) power transmission. The 48-hour course is for students entering post-high school pretechnical education programs without basic high school physics. The teacher should be qualifed to teach physics. This mimeographed document lists two suggested texts and two references. (hc)
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; Physics; Postsecondary Education; Pretechnology Programs; Vocational Education